Long-term follow-up of patients with deferred coronary intervention guided by measurement of fractional flow reserve - Luísa Vilalonga Pereira (Revista Portuguesa de Cardiologia (English Edition), 2013)
Introduction and Aims: The functional significance of coronary lesions can be assessed in the cardiac catheterization laboratory by determination of fractional flow reserve (FFR), thus overcoming one of the major limitations of conventional angiography. The aim of this study was to analyze the long-term clinical course of patients with intermediate coronary stenosis (50–70%) deferred for intervention based on FFR <0.80. Methods: Between May 1999 and December 2009, 300 lesions in 231 patients (mean age 65±10 years, 68% male and 75.3% with multivessel disease) were studied by FFR. Intervention was deferred in 282 (94%) lesions and 18 were treated based on FFR <0.80. We assessed the occurrence of major adverse cardiovascular events (MACE), defined as cardiovascular death, non-fatal acute coronary syndrome and target lesion revascularization (TLR). Results: During a median follow-up of 637 days (interquartile range 455–1160), there were 15 (6.5%) MACE in the subgroup of patients with target lesion intervention deferred based on FFR: one cardiovascular death, four hospitalizations for acute coronary syndrome and 14 TLR (12 patients were treated percutaneously and two underwent coronary artery bypass grafting). MACE-free survival at one year follow-up was 97.8%. Conclusion: These results, in a real-world population, support the current trend to base the decision to treat on functional rather than purely anatomical criteria, in order to improve safety and efficiency. Resumo: Introdução e objetivos: No laboratório de cardiologia de intervenção é possível efetuar avaliação do significado funcional de lesões coronárias com recurso à determinação da fração do fluxo de reserva coronária por guia de pressão (FFR) e assim ultrapassar uma das limitações principais da angiografia convencional.O objetivo foi analisar a evolução clínica a longo prazo de doentes submetidos a cateterismo cardíaco no qual se detetaram estenoses coronárias de gravidade intermédia (50-70%) e nas quais a intervenção foi diferida com base no resultado de FFR <0,80. Métodos: Entre maio de 1999 e dezembro de 2009 foram avaliadas por FFR 300 lesões em 231 doentes (idade média 65 ± 10 anos, 68% sexo masculino e 75% doença multivaso). Das 300 lesões estudadas por FFR, a intervenção foi diferida em 282 (94%), tendo sido intervencionadas 18, por apresentarem FFR <0,80. Avaliámos a ocorrência de eventos cardiovasculares major (MACE), definidos como o end point combinado de morte cardiovascular, síndrome coronária aguda (SCA) não fatal e revascularização da lesão alvo (TLR). Resultados: Ao longo de uma mediana de seguimento de 637 [IQR 455-1160] dias ocorreram 15 (6,5%) MACE no subgrupo de doentes com lesão alvo diferida com base no valor do FFR: uma morte cardiovascular, quatro internamentos por SCA e 14 TLR (12 doentes revascularizados de forma percutânea e dois submetidos a CABG). A sobrevida livre de MACE a um ano foi de 97,8%. Conclusão: Os achados deste estudo relativo a uma população do mundo real consolidam a tendência atual para que a decisão de intervir se baseie em critérios funcionais e não meramente anatómicos, que garantam segurança e eficiência. Keywords: Fractional flow reserve, Ischemia, Angioplasty, Stent, Palavras-chave: Fração do fluxo de reserva coronária, Isquémia, Angioplastia, Stent